Philippine Food Security Paradoxities Exposed: Exploring Structural Inequities and Pathways to Sovereignty - Servaña, Alvin; Manalastas, Katya (New Countryside, 2025)
This essay critically examines the persistent food security challenges in the Philippines, a nation paradoxically rich in agricultural resources yet plagued by hunger and malnutrition. Through a comprehensive four-part analysis, it systematically unpacks the complex milieus: historical, economic, political—factors shaping this crisis. Part 1 explores the historical and contemporary dynamics driving the hunger for food sovereignty, examining how export-oriented agriculture—driven by global actors, i.e., multinational corporations and international financial—has systematically marginalised small-scale farmers and eroded local food systems. Part 2 leverages Renato and Letizia Constantino’s “Distorted Priorities: The Politics of Food” to analyse the historical continuities between colonial and contemporary agricultural policies, while employing Foucault’s concepts of biopolitics and governmentality to illuminate the regulatory mechanisms perpetuating these inequities. The analysis reveals how cultural imperialism propagated by fast food chains and environmental degradation caused by monoculture farming have further complicated the nation’s food security landscape. Part 3 applies Iris Marion Young’s “Five Faces of Oppression” framework to systematically analyse exploitation, marginalisation, powerlessness, cultural imperialism, and structural violence within the Philippine food system. Part 4 synthesises these perspectives to examine critical implications for food sovereignty and proposes transformative approaches through food sovereignty principles, genuine agrarian reform, and sustainable agricultural practices. The essay concludes that by addressing structural inequalities and empowering marginalised communities through comprehensive policy reforms and grassroots initiatives, the Philippines can move towards a future where all individuals have access to nutritious, affordable, and culturally appropriate food, reflecting a commitment to social justice and environmental sustainability